Treatment of hidradenitis suppurativa with 755-nm alexandrite laser hair removal: A randomized controlled trialCapsule Summary - Seraphima Sidhom, MS; Sarah Utz Petry, MD; Rachel Ward, MD; Steven Daveluy, MD (Elsevier, 2024)
Background: Hidradenitis supprativa is a chronic inflammatory skin disease that can respond to treatment with laser hair removal. Objective: To assess alexandrite laser hair removal laser as a treatment for hidradenitis suppurativa as measured by the Hidradenitis Supprativa Clinical Response. Materials and methods: We conducted a prospective, randomized, controlled study in adult patients with hidradenitis supprativa. Participants underwent a series of 4 monthly laser treatments to 1 side of the body, with the contralateral side serving as a control. The primary outcome was Hidradenitis Supprativa Clinical Response at week 24, 8 weeks after the final laser treatment. Results: The percent improvement across treated sites after 4 treatments was 72.73% axillary, 70% inguinal, and 100% inframammary. Across all body regions, Hidradenitis Supprativa Clinical Response was significantly higher for the sites treated with the alexandrite laser compared to the contralateral controls: 75% vs 33.33% (P = .0046, 95% CI: [0.16, 1]). Limitations: The limitations of this study include a small sample size from which the data was collected. Conclusions: The 775-nm alexandrite laser is a safe and effective treatment for hidradenitis supprativa at various anatomic sites in both resolving preexisting lesions and preventing new eruptions.